The Exploration Of Coping Skills In Bonjok Lor Village In Leisure Activities In The Pandemic Covid-19 - Dzafira Indarsyah Madysari; Endang Sri Wahyuni (Jurnal Keterapian Fisik, 2021)
Background: The COVID-19 pandemic caused social disturbances that have an impact on physical activity in the elderly, especially in doing leisure time, so that appropriate coping skills are needed to overcome various disorders in recreational activities so that the elderly do not have an impact on psychological disorders. The purpose of this study was to analyze recreational activities carried out as well as strategies for the elderly's coping skills in carrying out recreational activities during the COVID-19 pandemic. Methods: This research is qualitative research with a phenomenological perspective. Methods of in-depth interviews and documentation. Data were obtained through in-depth interviews with 8 elderly informants in Bonjok Lor Village, Bonorowo District, Kebumen Regency who have met the criteria (able to communicate well; elderly who are not actively working/retired; helping research informants). The data analysis technique used method triangulation and theoretical triangulation. Results: There was a change in the leisure of the elderly between before and before the COVID-19 pandemic. This triggers a change in the goals of the elderly in doing recreational activities. On the other hand, the COVID-19 pandemic poses various problems for the elderly, such as psychological problems, health problems, disturbances in carrying out activities, and compliance with health protocols. Appropriate coping skills strategies are needed, such as; task-oriented coping, emotion-oriented coping, avoidance-oriented coping with the aim that the elderly can still carry out recreational activities during the COVID-19 pandemic. Conclusion: Changes in recreational activities and the goals of the elderly in doing recreation during the COVID-19 pandemic trigger various problems, therefore skills are needed to overcome the right strategies so that the elderly can benefit from doing recreational activities during the COVID-19 pandemic.